Prognostic indices in diffuse large B‐cell lymphoma in the rituximab era: an analysis of the UK National Cancer Research Institute R‐CHOP 14 versus 21 phase 3 trial. (20th May 2020) - Gleeson, Mary; Counsell, Nicholas; Cunningham, David; Lawrie, Anthony; Clifton‐Hadley, Laura; Hawkes, Eliza; McMillan, Andrew; Ardeshna, Kirit M.; Burton, Cathy; Chadwick, Nick; Gambell, Joanna; Smith, Paul; et al.
Summary: We compared the International Prognostic Index (IPI), Revised (R)‐IPI and age‐adjusted (aa)‐IPI as prognostic indices for patients with diffuse large B‐cell lymphoma (DLBCL) in the UK National Cancer Research Institute (NCRI) R‐CHOP 14 versus 21 trial ( N  = 1080). The R‐IPI and aa‐IPI showed no marked improvement compared to the IPI for overall and progression‐free survival, in terms of model fit or discrimination. Similar results were observed in exploratory analyses incorporating the Grupo Español de Linfomas/Transplante de Médula Ósea (GELTAMO)‐IPI, where baseline β2‐microglobulin data were available ( N  = 655). Although our findings support current use of the IPI, a novel prognostic tool to better delineate a high‐risk DLBCL group in the rituximab era is needed.